THE LABORATORY SYSTEM TO ANALYZING POWER INVERTERS DURING VOLTAGE SAG - Zieliński, Dariusz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The effective usage of the renewable energy is the topic that nowadays is more and more frequently discussed due to the fact that the demands made by the users concerning the payback period and the reliability of the components parts are constantly increasing. To achieve this, it is advisable to maximally increase the effectiveness of the converting systems and adjust them to the operation with the dynamically variable parameters of the power grid (i.e. by the application of the complex algorithms of vector steering). Such solutions lead to the effective conversion of the energy and the safe operation even during strong interference coming from the power grid. In the article, the author focuses on the important element of the converting system which is the synchronizing algorithm of the converter with the network (PLL). The article provides the results of the research conducted on the PLL algorithm simulated in the Matlab/Simulink software. Moreover, it outlines the comparison between the simulation results and the results obtained during the research on the real converter cooperating with the network model. The attractiveness of the presented article is increased by the application of the authorial emulator of the power grid.